The PERCEIVE quantitative study: PrEdiction of Risk and Communication of outcome following major lower-limb amputation: protocol for a collaboratiVE study. Issue 6 (30th November 2021) - Gwilym, Brenig L; Waldron, Cherry-Ann; Thomas-Jones, Emma; Preece, Ryan; Milosevic, Sarah; Brookes-Howell, Lucy; Pallmann, Philip; Harris, Debbie; Massey, Ian; Burton, Jo; Stewart, Philippa; Samuel, Katie; et al.
Abstract: Background: Accurate prediction of outcomes following surgery with high morbidity and mortality rates is essential for informed shared decision-making between patients and clinicians. It is unknown how accurately healthcare professionals predict outcomes following major lower-limb amputation (MLLA). Several MLLA outcome-prediction tools have been developed. These could be valuable in clinical practice, but most require validation in independent cohorts before routine clinical use can be recommended. The primary aim of this study is to evaluate the accuracy of healthcare professionals' predictions of outcomes in adult patients undergoing MLLA for complications of chronic limb-threatening ischaemia (CLTI) or diabetes. Secondary aims include the validation of existing outcome-prediction tools. Method: This study is an international, multicentre prospective observational study including adult patients undergoing a primary MLLA for CLTI or diabetes. Healthcare professionals' accuracy in predicting outcomes at 30-days (death, morbidity and MLLA revision) and 1-year (death, MLLA revision and ambulation) will be evaluated. Sixteen existing outcome-prediction tools specific to MLLA will be examined for validity. Data collection began on 1 October 2020; the end of follow-up will be 1 May 2022. The C-statistic, Hosmer–Lemeshow test, reclassification tables and Brier score will be used to evaluate the predictive performance of healthcare professionals and prediction tools, respectively. Study registration and dissemination: This study will be registered locally at each centre in accordance with local policies before commencing data collection, overseen by local clinician leads. Results will be disseminated to all centres, and any subsequent presentation(s) and/or publication(s) will follow a collaborative co-authorship model. Abstract : PERCEIVE (PrEdiction of Risk and Communication of outcome following major lower limb amputation—a collaboratiVE study) is an international, multicentre prospective observational study including adult patients undergoing a primary major lower-limb amputation (MLLA) for chronic limb-threatening ischaemia (CLTI) or diabetes. It aims to evaluate the accuracy of healthcare professionals' predictions of outcomes in adult patients undergoing MLLA for complications of CLTI or diabetes. Secondary aims include the validation of existing outcome-prediction tools in this patient cohort.